2000
DOI: 10.2105/ajph.90.5.797
|View full text |Cite
|
Sign up to set email alerts
|

Plastic wall materials in the home and respiratory health in young children

Abstract: Objectives. The relation between the presence of plastic wall materials in the home and respiratory health in children was assessed.Methods. This population-based cross-sectional study involved 2568 Finnish children aged 1 to 7 years.Results. In logistic regression models, lower respiratory tract symptoms-persistent wheezing (adjusted odds ratio [OR]=3.42, 95% confidence interval [CI] = 1.13, 10.36), cough (OR = 2.41, 95% CI = 1. 04, 5.63), and phlegm (OR = 2.76, 95% CI = 1.03, 7.41)-were strongly related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…While a recent study in Sweden also found higher urinary phthalate metabolite concentrations in infants in homes with vinyl flooring as compared to those without, 34 our study adds a demonstrated link between “vinyl or linoleum” flooring to higher air concentrations to higher urinary metabolite concentrations, thus strengthening the evidence for an airborne exposure pathway through which vinyl flooring may contribute to internal dose. Our findings that vinyl flooring may contribute via indoor air to children’s exposure to BBzP but not DEHP suggests that prior studies showing an association between vinyl flooring and children’s incident asthma 3, 35 and respiratory symptoms 4, 5 may be due to BBzP exposure. Thus, the additional understanding of sources of exposure and their contribution to measures of MBzP may fill a gap in the current scientific literature by providing a link between previous observations about flooring and respiratory symptoms and asthma.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…While a recent study in Sweden also found higher urinary phthalate metabolite concentrations in infants in homes with vinyl flooring as compared to those without, 34 our study adds a demonstrated link between “vinyl or linoleum” flooring to higher air concentrations to higher urinary metabolite concentrations, thus strengthening the evidence for an airborne exposure pathway through which vinyl flooring may contribute to internal dose. Our findings that vinyl flooring may contribute via indoor air to children’s exposure to BBzP but not DEHP suggests that prior studies showing an association between vinyl flooring and children’s incident asthma 3, 35 and respiratory symptoms 4, 5 may be due to BBzP exposure. Thus, the additional understanding of sources of exposure and their contribution to measures of MBzP may fill a gap in the current scientific literature by providing a link between previous observations about flooring and respiratory symptoms and asthma.…”
Section: Discussionmentioning
confidence: 52%
“…3 Plastic wall materials also have been associated cross-sectionally with bronchial obstruction and persistent wheeze in children. 4, 5 The presumed important role of the phthalates in these epidemiologic associations between flooring and respiratory health has also spurred biomonitoring to better understand the specific sources, routes and health effects of the phthalate plasticizers. 2, 6 We recently reported that prenatal urinary butylbenzyl phthalate (BBzP) metabolite concentrations were associated with incident childhood asthma 7 and that children’s urinary BBzP metabolite concentrations were associated cross-sectionally with airway inflammation in a New York City cohort.…”
Section: Introductionmentioning
confidence: 99%
“…The Finnish (Jaakkola et al 2000) and the Russian studies (Jaakkola et al 2004) and the first phase of the Swedish study (Bornehag et al 2004a, 2005) were population-based cross-sectional studies. The Norwegian study (Jaakkola et al 1999; Øie et al 1999) was a one-to-one matched case–control study, and the second phase of the Swedish study (Bornehag et al 2004b) was a case–control study.…”
Section: Resultsmentioning
confidence: 99%
“…Greater household dust concentrations of butyl-benzyl phthalate and di(2-ethylhexyl) phthalate (DEHP) were found among Swedish children with rhinitis, eczema, or asthma than in children without allergic symptoms. 4 The amount of PVC plastic flooring and wall coverings has been associated with bronchial obstruction 5 and asthma 6 among Norwegian and Finish children, respectively. House dust concentrations of DEHP are higher in homes with more PVC plastic, 7 suggesting that the observed effect of plastic wall coverings may be mediated by phthalate exposure.…”
mentioning
confidence: 99%